The effect of synbiotics on liver enzymes, obesity indices, blood pressure, lipid profile, and inflammation in patients with non-alcoholic fatty liver: A systematic review and meta-analysis of randomized controlled trials - Vali Musazadeh; Kimia Assadian; Fatemeh Rajabi; Amir Hossein Faghfouri; Yosra Soleymani; Zeynab Kavyani; Behnam Najafiyan (Elsevier, 2024)
Background: Patients with non-alcoholic fatty liver disease (NAFLD) benefit from using synbiotics. However, findings from existing trials remain contentious. Therefore, this meta-analysis evaluated the effects of synbiotics on liver enzymes, blood pressure, inflammation, and lipid profiles in patients with NAFLD. Methods: We searched PubMed, Embase, Cochrane, Scopus, and Web of Science for randomized controlled trials (RCTs) regarding synbiotics supplementation in patients with NAFLD. Results: The meta-analysis revealed that synbiotics supplementation significantly improved liver enzymes (AST, WMD: −9.12 IU/L; 95 % CI: −13.19 to −5.05; ALT, WMD: −8.53 IU/L; 95 % CI: −15.07 to −1.99; GGT, WMD: −10.42 IU/L; 95 % CI: −15.19 to −5.65), lipid profile (TC, WMD: −7.74 mg/dL; 95 % CI: −12.56 to −2.92), obesity indices (body weight, WMD: −1.95 kg; 95 % CI: −3.69 to −0.22; WC, WMD: −1.40 cm; 95 % CI: −2.71 to −0.10), systolic blood pressure (SBP, WMD: −6.00 mmHg; 95 % CI: −11.52 to −0.49), and inflammatory markers (CRP, WMD: −0.69 mg/L; 95 % CI: −1.17 to −0.21; TNF-α, WMD: −14.01 pg/mL; 95 % CI: −21.81 to −6.20). Conclusion: Overall, supplementation with synbiotics positively improved liver enzymes, obesity indices, and inflammatory cytokines in patients with NAFLD.